Threat patterns and conservation status of endemic vascular flora in Argentina: a quantitative perspective - Salariato, Diego L.; Zanotti, Christian; Zuloaga, Fernando O. (Phytotaxa, 2021)
Global warming, coupled with habitat destruction and human activity, are accelerating the rates of species extinction worldwide. Species-extinction risk assessment, using the IUCN Red List categories, together with the study of the spatial patterns of biodiversity, are fundamental approaches to identify conservation priorities and targeting government decisions to mitigate impacts on biodiversity. Here, we analyzed threat levels of endemic species for the entire Argentinean vascular flora. Accordingly, we classified species following the IUCN threat categories and analyzed threat levels within different families, plant life-forms, and biogeographic regions of the country. We also analyzed spatial patterns of threat by means of macroecological modeling techniques and explored the effectiveness of current protected areas in relation to the threatened endemics they actually included. The results showed that of the 1683 Argentinean endemic vascular plant taxa, 800 species were categorized under threat (VU, EN, or CR) ( 47%). Families with the highest number of threatened species were also those with the highest number of endemics; herbs and climbing plants presented significantly higher threat levels, and among biogeographic provinces, the most affected in terms of threat proportion were the Altoandina, Yungas, and Paranaense. In addition, different hotspots of threatened endemism were detected, mainly associated with mountainous areas with high altitudinal heterogeneity; of these, only nearly half of the hotspots are included, at least partially, within a protected area. An up-to-date species list of Argentinean endemic plants, including their proposed conservation status, is also provided. This work seeks to contribute to the knowledge on geographical patterns of the Argentinean flora and its conservation, complementing the information published in the Flora of Argentina.